The Role of Business Size and Technology Adoption in Enhancing MSME Financial Performance - Yulianto Umar Rofi'i (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This study examines the impact of business size and technology adoption on the financial performance of SMEs (Small and Medium Enterprises). Business size is measured based on operational scale, such as the number of employees and sales volume. At the same time, technology adoption refers to using digital tools and information systems in business operations. Multiple linear regression is applied to analyze data collected from 100 SMEs across various industries. The analysis results show that business size significantly positively affects financial performance, with a regression coefficient of 0.35 (p-value = 0.002). This means that increasing business size will drive an improvement in economic performance. Technology adoption also has a significant impact, with a regression coefficient of 0.42 (p-value = 0.001), indicating that the use of technology can enhance financial performance. The coefficient of determination (R²) of 0.58 suggests that 58% of the variation in economic performance can be explained by business size and technology adoption. These findings are important for SME owners and policymakers to design strategies to accelerate SMEs' growth and sustainability through business scaling and digital technology implementation.